TINGKAT BAHAYA EROSI PADA TIAP SATUAN LAHAN DI DAERAH ALIRAN SUNGAI KANAIKAN BAGIAN HULU KABUPATEN PASAMAN BARAT - Arif Fiandi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
The purpose of this study to analyze and describe data on rainfall, erosivitis rainfall, soil characteristics and the level of erosion hazard in the watershed upstream part of the increase in West Pasaman. This research is classified as descriptive and the method used is survey method with the sample area. Sampling in the retractable in purposive sampling with a selected sample of 10 units of land that is considered to represent the research area. The results showed 1) the characteristics of the land, namely soil texture, slope and slope length greatly affect the rate of erosion in the watershed hike upstream, 2) the level of erosion erosion hazard in the watershed increase in the upstream part there are three main categories of erosion potential moderate, severe and very severe, 3 ) high erosion in the watershed upstream part due to the rise in land clearing with a steep slope, the management of plants that are not accompanied by appropriate conservation measures and still the use of traditional measures.